Toilet Gender Neutral In LGBT Practices: A Comparative Study Of Human Rights And Religion - Sumardi Sumardi*; Susilawati Susilawati; Achmad Napis Qurtubi; Syahrianti Syam; Rica Regina Novianty (Riwayat: Educational Journal of History and Humanities, 2023)
Discussion of LGBT continues to be a debate among the world community. This study aims to compare the perspectives of human rights and religion in examining gender-neutral toilets in LGBT practices. This research is qualitative research with descriptive methods. The primary data source used in this study is data regarding alleged LGBT practices at Jakarta's international schools. While the secondary data sources used in this study are previous studies that are relevant to the research. The data analysis technique used in this research is data presentation, data reduction, and concluding the perspective of Miles and Huberman. The results of this study indicate that the problem of gender-neutral toilets based on human rights based on international law shows support for LGBT practices, while religions based on pure legal sources such as the Qur'an and hadith strictly prohibit gender-neutral toilet facilities that support LGBT practices. Studies on LGBT in Indonesia need to be taken seriously to obtain clarity and a legal basis that can suppress the development of LGBT.